The Late Stage of Human Immunodeficiency Virus Type 1 Assembly Is an Energy-Dependent Process - Tritel, Marc (American Society for Microbiology, 2001)
Several recent studies have indicated the involvement of host cell factors in human immunodeficiency virus type 1 (HIV-1) assembly. To ascertain whether ATP-dependent factors play a role in this process, we quantified virus-like particle (VLP) production by ATP-depleted cells. Pharmacological ATP depletion abrogated VLP production without affecting cell viability or inducing degradation of HIV-1 Gag protein. This effect occurred even when the ATP-depleting agents were added 1 h into the assembly process, and it was reversed by removal of these agents. ATP depletion did not affect Gag membrane binding or multimerization. Density gradient analysis indicated that HIV-1 assembly intermediates were stalled late in the assembly process. This conclusion was further supported by electron microscopy analysis, which revealed a preponderance of plasma membrane-associated stalk-like structures in the ATP-depleted cells. Since no HIV-1 proteins bind or hydrolyze ATP, these findings indicate that an ATP-requiring cellular factor is an obligatory participant late in the HIV-1 assembly process.